KEMAMPUAN TANAMAN APU- APU (Pistia stratiotes L.) DALAM MENURUNKAN KADAR LOGAM BERAT NIKEL (Ni) LIMBAH CAIR - Lestari Dwi Utami; Narwati .; Umi Rahayu (GEMA LINGKUNGAN KESEHATAN, 2017)
ABSTRACTResearch on reduction of Nickel (Ni) heavy metal in wastewater by using a water plant lettuce (Pistiastratiotes L.) was conducted with the aim of knowing the level of Ni reduction in wastewater after the plants aregiven water plant lettuce (Pistia stratiotes L.). The technique used in processing wastewater of the metal platingis phytoremediation.This study was pure experiment with pretest-posttest design with control group used completerandomized design (CRD). This study was conducted in December to June, 2016.The results showed that the level of Ni in wastewater decreased after 1 day, 3 day and 6 day treatmentwith water plant lettuce. From the statistical test result, the reduction of Ni was significant with 5 plants by p =0.023 α. Based on the contact time duration, the result of statistical test was p = 0.000 α. The more thenumber of plants used, the greater the reduction of Nickel level. The longer the contact time of the water plantwith wastewater, the greater the reduction of Nickel level in wastewater.For further study, it is suggested to use plant that is hyper tolerant against contaminants and usedmore plants to proceed wastewater and more comparable with the level of Ni metal contained in wastewatermetal plating.Keywords : Nickel level reduction, water plant lettuce (Pistia stratiotes L.),contact duration, phytoremediation.